Health Traditions for Pregnant Women and Perspectives on Postpartum Visits in the Coastal Area of ​​Fishermen's Villages, Medan Belawan District - Nurhayati, Nurhayati; Jauhari, Anjani; Damanik, Syahbrina Meisela; Ramadhani, Nabilla Suci (CV. Rayyan Dwi Bharata, 2024)
Postpartum visit is one of the health services for pregnant women who experience the postpartum period which aims to improve the health, and knowledge of pregnant women related to postpartum care. The purpose of this study was to determine how the culture and tradition of health in pregnant women in Fishermen Village. This research was conducted in Kampung Nelayan Sebrang Lingkungan 12, Belawan 1 Urban Village, Medan Belawan District, North Sumatra. The method used in this research is exploratory research using qualitative design and a descriptive phenomenological approach to examine information about pregnancy, childbirth, postpartum care, as well as community customs in carrying out care. Data collection techniques in this study were carried out by interviews in order to directly understand the problems that occur in the area and documentation studies. The results obtained from this study show that the community in Kampung Nelayan still applies several cultures and traditions of pregnant women passed down from their ancestors. Such as wearing octopus and pilis on the forehead of mothers and newborn babies and postpartum visits in Kampung Nelayan are also applied to postpartum pregnant women and they respond well to these visits, and with these visits the community feels very helpful.